Experimental investigation of a multilayer detention roof for stormwater management. (1st April 2023) - Alim, Mohammad A.; Jahan, Sayka; Rahman, Ataur; Rahman, Mohammad Ataur; Liebman, Mark; Garner, Brad; Griffith, Robert; Griffith, Merran; Tao, Zhong
Abstract: This study aimed to evaluate the technical feasibility of a multilayer detention roof, namely a purple roof, in managing urban stormwater. A purple roof is conceptually and technically different from a green roof in that the former includes a low-transmissivity drainage layer and a void layer that can be designed at various depths for the temporary storage and slow release of water. Three types of roofs, i.e., (i) traditional, (ii) green and (iii) purple, were constructed in Western Sydney, Australia. These roofs were investigated and compared in terms of runoff reduction capacity, time to start runoff and time to release the runoff. Data were collected across the period from April 2021 to May 2022. A total of 76 rainfall events were recorded during this period. It was found that the purple roof performed better than other roof systems during all the rainfall events. The purple roof delayed the median start times of runoff by 773, 211 and 86 min for small, medium and large rainfall events, respectively, compared to a traditional roof, and 110, 59 and 14 min, respectively, compared to a green roof. During small rainfall events, the purple roof retained 100% of the water on most occasions. For medium, large, and extremely large events, the median runoff volume reductions by the purple roof were 88%, 34% and 7%, and 55%, 21% and 10% than those of the traditional and green roofs, respectively. In addition to reducing the volume discharged, the purple roof took 242 and 113 min (median values) longer to discharge the stormwater compared to the traditional roof during medium and large events, respectively, and 226 and 66 min (median values) longer than the green roof. In the case of median times for extremely large events, the purple roof took 503 min longer to release stormwater than the traditional roof, and 74 min longer than the green roof. The outcomes from this study proved the technical feasibility of the purple roof technology to slow the release and reduce the volume of stormwater during different-sized rainfall events. Thus, a purple roof can potentially be used to replace the traditional detention basins in a dense urban environment to reduce flood risks. Graphical abstract: Image 1 Highlights: Purple roof can delay the start of runoff for most rainfall events. During small rainfall events, purple roof retains 100% of runoff. Purple roof outperforms the traditional and green roofs in retaining runoff.